1995
DOI: 10.1128/jcm.33.12.3115-3118.1995
|View full text |Cite
|
Sign up to set email alerts
|

Plasma (1-->3)-beta-D-glucan and fungal antigenemia in patients with candidemia, aspergillosis, and cryptococcosis

Abstract: ␤-D-Glucan is one of the major structural components of fungi, and it seems that it can be detected by the fractionated (133)-␤-D-glucan-sensitive component from a Limulus lysate, factor G. We evaluated the concentration of (133)-␤-D-glucan by using factor G and other fungal antigens in 24 patients with clinical evidence of mycosis and 36 healthy subjects. The mean concentration of (133)-␤-D-glucan in the plasma of the healthy subjects was found to be 2.7 ؎ 1.9 pg/ml (range, <6.9 pg/ml), and it was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(73 citation statements)
references
References 20 publications
(27 reference statements)
1
68
0
4
Order By: Relevance
“…3)-glucan-sensitive factor G of the horseshoe crab coagulation enzyme is useful for the screening of general fungal infections [12]. It is reported that patients with deep mycosis such as candidasis, aspergillosis, trichosporosis and carinii pneumonia but 0928 not mucormycosis or cryptococcosis show a positive reaction correlated with clinical symptoms and pathological changes [13][14][15]. Also, it was reported that b-(1 !…”
Section: Introductionmentioning
confidence: 99%
“…3)-glucan-sensitive factor G of the horseshoe crab coagulation enzyme is useful for the screening of general fungal infections [12]. It is reported that patients with deep mycosis such as candidasis, aspergillosis, trichosporosis and carinii pneumonia but 0928 not mucormycosis or cryptococcosis show a positive reaction correlated with clinical symptoms and pathological changes [13][14][15]. Also, it was reported that b-(1 !…”
Section: Introductionmentioning
confidence: 99%
“…To diagnose deep-seated fungal infections, a (1C3)-L-D-glucan-speci¢c chromogenic kit (Fungitec G test MK) has been developed and applied clinically [11^13]. The soluble L-glucan in sera must be a metabolite of Candida [14,15]. By batch culture, Candida produced L-glucan in the culture supernatant, but the yield was low compared with the content of the cell wall Lglucan which is essentially water insoluble [16].…”
Section: Introductionmentioning
confidence: 99%
“…Detection of a number of fungal-specific antigens in serum and other body fluids has proved to be useful in the serodiagnosis of invasive fungal disease (Dupont et al, 1987;Haynes et al, 1990;Miyazaki et al, 1995;Gomez et al, 1999). The identification and characterization of extracellular cryptococcal PLB and the subsequent detection of anti-PLB IgG in serum of infected patients (Chen et al, 2000;Santangelo et al, 2005) raised the possibility that PLB may be secreted into the bloodstream during active infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, elevated levels of (1 ! 3)b-D-glucan, a major structural component of fungal cell walls, are observed in plasma from patients with invasive candidiasis and aspergillosis, but not in patients with cryptococcosis (Miyazaki et al, 1995). Cryptococci, unlike Candida and Aspergillus cells, shed only small amounts of (1 !…”
Section: Discussionmentioning
confidence: 99%